Effects of 6 weeks core training on balance, strength and service performance in volleyball players - Yapici, A. (European Journal of Physical Education and Sport Science, 2019)
The aim of this study is to investigate the effects of 6 weeks core exercises on balance, strength and service performance. This study was conducted on 32 female volleyball players who played in Denizlispor A team. 16 experimental group (average age 16,62±1.04 years; mean body height 164.62±8.72 cm; mean body mass 54.69±8.56 kg) and 16 control group (average age 16.71±1.34 years; mean body height 169±7.88 cm; mean body mass 55.63±8.25 kg) participated in this study voluntarily. For each player, core strength, static and dynamic balance, service accuracy score test and velocity of the service performance was measured. All test measurements of the experimental and control groups were carried out before and after the 6-week training program. Mann Whitney U test for paired comparison of the groups and Wilcoxcon test for the comparison of pre- and post-tests of the groups were used. The significance level was taken as p<0.05. There was no statistically significant difference between the pre-test values of all measurements of the experimental and control groups (p>0.05). There was a statistically significant difference between the pre and post-test values of the experimental group between right-left leg dynamic balance, core strength values, service accuracy score test performance and velocity of the service performance values (p<0.05). There was no statistically significant difference between static balance values (p>0.05). There was statistically significant difference between the post-test right-left leg dynamic balance, core strength values, service accuracy score test performance and velocity of the service performance in experimental and control groups (p<0.05). The results of this study; taking into account the possible effects of strength training on the athletes on the trainers' core training programs, they should be included in volleyball season training as well as strength training.